An Integrated Multifunctional Nanoplatform for Deep‐Tissue Dual‐Mode Imaging. (22nd January 2018) - Yang, Fan; Skripka, Artiom; Benayas, Antonio; Dong, Xianke; Hong, Sung Hwa; Ren, Fuqiang; Oh, Jung Kwon; Liu, Xinyu; Vetrone, Fiorenzo; Ma, Dongling
Abstract: The combination of biocompatible superparamagnetic and photoluminescent nanoparticles (NPs) is intensively studied as highly promising multifunctional (magnetic confinement and targeting, imaging, etc.) tools in biomedical applications. However, most of these hybrid NPs exhibit low signal contrast and shallow tissue penetration for optical imaging due to tissue‐induced optical extinction and autofluorescence, since in many cases, their photoluminescent components emit in the visible spectral range. Yet, the search for multifunctional NPs suitable for high photoluminescence signal‐to‐noise ratio, deep‐tissue imaging is still ongoing. Herein, a biocompatible core/shell/shell sandwich structured Fe3 O4 @SiO2 @NaYF4 :Nd 3+ nanoplatform possessing excellent superparamagnetic and near‐infrared (excitation) to near‐infrared (emission), i.e., NIR‐to‐NIR photoluminescence properties is developed. They can be rapidly magnetically confined, allowing the NIR photoluminescence signal to be detected through a tissue as thick as 13 mm, accompanied by high T2 relaxivity in magnetic resonance imaging. The fact that both the excitation and emission wavelengths of these NPs are in the optically transparent biological windows, along with excellent photostability, fast magnetic response, significant T2 ‐contrast enhancement, and negligible cytotoxicity, makes them extremely promising for use in high‐resolution, deep‐tissue dual‐mode (optical and magnetic resonance) in vivo imaging and magnetic‐driven applications. Abstract : Core/shell/shell Fe3 O4 @SiO2 @NaYF4 :Nd 3+ nanoplatforms possess excellent superparamagnetic and near‐infrared (excitation) to near‐infrared (emission) photoluminescence properties, which allow the NIR photoluminescence signal to be detected through a tissue as thick as 13 mm. These features make them extremely promising for use in high‐resolution, deep‐tissue dual‐mode (optical and magnetic resonance) imaging in vivo.